2008
DOI: 10.1056/nejmoa0801485
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting or Bare-Metal Stents for Acute Myocardial Infarction

Abstract: In patients presenting with acute myocardial infarction, treatment with drug-eluting stents is associated with decreased 2-year mortality rates and a reduction in the need for repeat revascularization procedures as compared with treatment with bare-metal stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(123 citation statements)
references
References 27 publications
4
114
1
4
Order By: Relevance
“…110 Compared with balloon angioplasty, routine BMS implantation during primary PCI decreases risk for TVR and possibly reduces MI rates but does not reduce mortality rates. 111,112 Two-year data from the Massachusetts registry 113 from 1221 propensity score-matched pairs of DES and BMS patients demonstrated a reduction in mortality and TVR rates with DES in primary PCI, and an analysis from the New York State registry 114 found a reduction in mortality rates but not TVR rates with DES. These reports were limited to patients treated More recently, several relatively small randomized clinical trials have shown an inconsistent efficacy for DES over BMS in primary PCI.…”
Section: Recommendations For the Use Of Stents In Stemimentioning
confidence: 99%
“…110 Compared with balloon angioplasty, routine BMS implantation during primary PCI decreases risk for TVR and possibly reduces MI rates but does not reduce mortality rates. 111,112 Two-year data from the Massachusetts registry 113 from 1221 propensity score-matched pairs of DES and BMS patients demonstrated a reduction in mortality and TVR rates with DES in primary PCI, and an analysis from the New York State registry 114 found a reduction in mortality rates but not TVR rates with DES. These reports were limited to patients treated More recently, several relatively small randomized clinical trials have shown an inconsistent efficacy for DES over BMS in primary PCI.…”
Section: Recommendations For the Use Of Stents In Stemimentioning
confidence: 99%
“…Hence, outcomes of studies performed favoured use of Bare Metal Stent (BMS) over DES. 11,12 However, meta-analysis presented a different view of various drug eluting stents. 13 The Horizon AMI and Horizon -III studies have demonstrated that rates of MACE and stent thrombosis are similar in DES and BMS.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there could be a relationship between the higher percentage of dialysis and lesion calci cation in the PES group. Secondly, several randomized studies have demonstrated the superiority of DESs over BMSs for the treatment of ACS 10 . However, during the era of rst-generation DESs, the use of DESs for ACS cases was debated due to the risk of late and very late stent thrombosis VLST [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%